High-heat-resistance hole sealing resin composition for graphite bipolar plate of hydrogen fuel cell and application of high-heat-resistance hole sealing resin composition
By using a high heat resistance resin composition on the hydrogen fuel cell graphite bipolar plate, the problem of softening of resin at high temperature in the prior art is solved, the heat resistance and mechanical strength of the fuel cell are improved, and the higher Airtight and environmentally friendly production process.
Patent Information
- Application Number
- CN202411630343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The resin glass transition temperature used in the prior art for the sealing of graphite bipolar plates is low, resulting in the resin softening under high temperature conditions, affecting the airtightness and mechanical strength of the fuel cell.
Provide a high heat resistance hydrogen fuel cell graphite bipolar plate sealing resin composition, including 70 to 90 wt% epoxy resin, 5 to 30 wt% diluent and 0 to 2 wt% additive, and 90 wt% The composition of ~99.5 wt% anhydride curing agent and 0.1 to 5 wt% accelerator ensures that the gel time is ≤5 minutes at 160°C, the glass transition temperature is >95°C and the surface tension is <30 mN/m.
It improves the heat resistance of graphite bipolar plates, avoids the resin softening at high temperatures, enhances the airtightness and mechanical strength of the fuel cell, reduces the generation of resin waste, and has environmental protection and cost advantages.
Smart Images

Figure CN119161695A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition and application thereof, belonging to the technical field of hydrogen fuel cells. Background Art
[0002] Hydrogen energy has attracted widespread attention due to its advantages such as no pollution, high calorific value and renewable nature. With the development of water electrolysis hydrogen production technology in recent years, as well as the continuous maturity of hydrogen storage and transportation technology, the application prospects of hydrogen energy are broader. Proton exchange membrane hydrogen fuel cells are one of its important application areas. It can directly convert the chemical energy in hydrogen into electrical energy through electrochemical reactions, with a theoretical conversion efficiency of 85~90%.
[0003] In proton exchange membrane hydrogen fuel cells, bipolar plates are an important component of the fuel cell stack. The weight and volume of bipolar plates account for about 80% of the proton exchange membrane fuel cell, and the cost is about 50%. The main functions of bipolar plates are to isolate and distribute oxidants and fuels, conduct current, support membrane electrodes, and regulate the internal temperature of the stack. Depending on the base material, bipolar plates are mainly divided into metal bipolar plates, graphite bipolar plates, and composite graphite bipolar plates. Among them, graphite bipolar plates have the advantages of high conductivity, high stability, and easy processing.
[0004] In graphite bipolar plates, the original graphite plates after high-temperature calcination and slicing have tiny holes of various shapes inside. These holes not only affect the air tightness and corrosion resistance of the bipolar plates, but also reduce their mechanical properties. Through resin impregnation filling and heating and curing, the resin can block the tiny holes and form a composite structure with graphite, which can solve problems such as air tightness and mechanical strength. Generally, low-viscosity epoxy resin compositions often have a low glass transition temperature, which is difficult to meet the heat resistance requirements of high-performance fuel cells. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the glass transition temperature of the resin used for sealing the graphite bipolar plates in the prior art is generally relatively low. When the fuel cell is under instantaneous high temperature or long-term over-temperature operation conditions, the resin changes from a glassy state to a rubbery state, causing the resin in the micropores to soften, the resin to separate from the inner wall of the graphite plate pores, and new gaps to appear, affecting the air tightness and mechanical strength of the fuel cell.
[0006] In order to solve the above technical problems, the present invention provides a high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition, the resin composition comprises a resin mixture and a curing agent mixture, the weight ratio of the resin mixture to the curing agent mixture is 100: (80~100); wherein the resin mixture comprises 70~90wt% of epoxy resin, 5~30wt% of diluent and 0~2wt% of auxiliary agent; the curing agent mixture comprises 90~99.5wt% of anhydride curing agent, 0.1~5wt% of accelerator and 0~5wt% of auxiliary agent; the diluent is a combination of glycerol ether diluent and alcohol diluent; The resin composition needs to meet the following properties: 1) Initial mixed viscosity ≤300mpa.s at 25℃; 2) The gel time of the resin composition at 160°C is ≤5min; 3) After the resin composition is cured at 140-160°C for 1-3 hours, the glass transition temperature is greater than 95°C; and 4) The surface tension of the resin composition is less than 30 mN / m.
[0007] Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, alicyclic epoxy resin, multifunctional epoxy resin, brominated epoxy resin and flexible long-chain toughened epoxy resin, and the epoxy equivalent of the epoxy resin is 100-400 g / equivalent; And / or, the auxiliary agent includes at least one of a coupling agent, a defoaming agent, a toughening agent, a thixotropic agent, a wetting agent, an antioxidant and a leveling agent.
[0008] More preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin and alicyclic epoxy resin, and the epoxy equivalent of the epoxy resin is 200-300 g / equivalent.
[0009] Preferably, the glyceryl ether diluent is selected from at least one of benzyl glycidyl ether, butyl glycidyl ether, octyl glycidyl ether, C12-C14 alkyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, dipropylene glycol diglycidyl ether, 1,2-cyclohexanediol diglycidyl ether, 1,4-cyclohexanediol diglycidyl ether, and pentaerythritol tetraglycidyl ether; The alcohol diluent is selected from at least one of benzyl alcohol, low molecular weight polypropylene glycol with a molecular weight of ≤2000 and low molecular weight polyethylene glycol with a molecular weight of ≤500.
[0010] Preferably, the anhydride curing agent is selected from at least one of phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, C8~C9 olefin succinic anhydride, dodecenyl succinic anhydride, methyl nadecanide, hydrogenated methyl nadecanide, tung oil anhydride, maleic anhydride, glutaric anhydride and methylenetetrahydrophthalic anhydride.
[0011] More preferably, the anhydride curing agent is selected from at least one of phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride and hydrogenated methylnadic anhydride.
[0012] Preferably, the accelerator is selected from o-hydroxybenzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, trioleate of 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 1,8-diaza-bicyclo(5,4,0)-7-undecene, 1,8-diaza-bicyclo(5,4,0)-7-undecene octanoate, 1,8-diaza-bicyclo(5,4,0)-7-undecene lactate, 1,8-diaza-bicyclo(5,4,0)-7-undecene phenolate, 1,8-diaza-bicyclo(5,4,0)-7-undecene phenolate. At least one of: 1,0-dihydro-2-nitro-1-yl-2-nitro-2-yl-4 ...
[0013] More preferably, the promoter is selected from at least one of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-phenyl-2-methylimidazole, 1-methylimidazole, 2-methylimidazole, 2,4-dimethylimidazole and 2,6-di-tert-butyl-p-cresol.
[0014] In some embodiments of the present invention, the resin composition comprises a resin mixture and a curing agent mixture in a weight ratio of 100:80~100, wherein the resin mixture comprises 70~80 parts of bisphenol A epoxy resin, 10~20 parts of alicyclic epoxy resin, 3~5 parts of 1,4-butanediol diglycidyl ether, 3~10 parts of polypropylene glycol, 0.1~0.3 parts of defoaming agent, and 0.05~0.2 parts of coupling agent; the curing agent mixture comprises 90~99 parts of methyltetrahydrophthalic anhydride, and 1~10 parts of 1-cyanoethyl-2-ethyl-4-methylimidazole.
[0015] In some other embodiments of the present invention, the resin composition comprises a resin mixture and a curing agent mixture in a weight ratio of 100:80~100, wherein the resin mixture comprises 40~60 parts of bisphenol A epoxy resin, 30~40 parts of bisphenol F epoxy resin, 9~11 parts of C12~C14 alkyl glycidyl ether, 4~6 parts of polyethylene glycol, 0.05~0.2 parts of defoaming agent, and 0.1~0.3 parts of coupling agent; the curing agent mixture comprises 85~95 parts of methyltetrahydrophthalic anhydride, 5~15 parts of phthalic anhydride, and 0.5~2 parts of 2,4,6-tris(dimethylaminomethyl)phenol.
[0016] The present invention also provides the use of the resin composition in sealing the pores of a graphite bipolar plate. The graphite bipolar plate is a graphite bipolar plate used in a hydrogen fuel cell.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition provided by the present invention has a high glass transition temperature after being heated and cured, which can meet the heat resistance requirements of the graphite bipolar plate of the proton exchange membrane fuel cell under instantaneous high temperature or long-term over-temperature operation conditions, and ensure that the resin will not soften and new pores will appear, thereby affecting the air tightness.
[0018] 2. The high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition provided by the present invention not only has the characteristics of high heat resistance, but also has the characteristics of low mixed viscosity, good fluidity and long operating time. Under room temperature impregnation conditions, it can avoid the resin from being difficult to impregnate into the tiny holes in the graphite plate due to the viscosity rising too quickly, thereby achieving the purpose of recycling, reducing the generation of resin waste, being environmentally friendly and reducing costs.
[0019] 3. The high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition provided by the present invention has outstanding chemical resistance in deionized water, 50% ethylene glycol solution, and a combined acidic solution of dilute sulfuric acid and hydrofluoric acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1It is the viscosity growth curve of the resin composition in Example and Comparative Example. DETAILED DESCRIPTION
[0021] In order to make the present invention more clearly understood, preferred embodiments are described in detail below with reference to the accompanying drawings.
[0022] In the following examples, the materials, reagents, etc. used are conventional commercially available products unless otherwise specified.
[0023] Example 1 A high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition comprises a resin mixture and a curing agent mixture, wherein the resin mixture comprises 74.7 parts of bisphenol A epoxy resin, 16 parts of alicyclic epoxy resin, 4 parts of 1,4-butanediol diglycidyl ether, 5 parts of polypropylene glycol with a molecular weight of 400, 0.2 parts of defoaming agent, and 0.1% of coupling agent; the curing agent mixture comprises 99 parts of methyltetrahydrophthalic anhydride and 1 part of 1-cyanoethyl-2-ethyl-4-methylimidazole.
[0024] The preparation method of the above resin composition is: (1) After accurately weighing bisphenol A epoxy resin, alicyclic epoxy resin, 1,4-butanediol diglycidyl ether, and polypropylene glycol according to the proportion, add them into a container, turn on the stirrer, and stir at a speed of 300 rpm for 15 minutes. After stirring, reduce the stirrer speed to 100 rpm, and then add defoaming agent and coupling agent dropwise while stirring. After the defoaming agent and coupling agent are added dropwise, continue stirring at a speed of 300 rpm for 15 minutes. Stop stirring after the resins are evenly mixed, and vacuum degas for standby use.
[0025] (2) Accurately weigh methyltetrahydrophthalic anhydride, pour it into a container, turn on the stirrer, set the speed to 200 rpm, and add 1-cyanoethyl-2-ethyl-4-methylimidazole dropwise while stirring. After the addition is completed, set the stirrer speed to 300 rpm and continue stirring for 15 minutes. Stop stirring after the curing agent is evenly mixed, and evacuate to remove bubbles for later use.
[0026] (3) The resin mixture of step (1) and the curing agent mixture of step (2) are uniformly mixed in a ratio of 100:90, and a high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition is obtained after degassing.
[0027] Example 2 A high-heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition comprises a resin mixture and a curing agent mixture, wherein the resin mixture comprises 50 parts of bisphenol A epoxy resin, 35 parts of bisphenol F epoxy resin, 9.7 parts of C12-C14 alkyl glycidyl ether, 5 parts of polyethylene glycol 200 (molecular weight of 190-210), 0.1 parts of defoaming agent, and 0.2 parts of coupling agent; and the curing agent mixture comprises 89 parts of methyltetrahydrophthalic anhydride, 10 parts of phthalic anhydride, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol.
[0028] The preparation method of the above resin composition is: (1) After accurately weighing bisphenol A epoxy resin, bisphenol F epoxy resin, C12~C14 alkyl glycidyl ether, and polyethylene glycol according to the proportion, add them into a container, turn on the stirrer, and stir at a speed of 300 rpm for 15 minutes. After stirring, reduce the stirrer speed to 100 rpm, and then add defoaming agent and coupling agent dropwise while stirring. After the defoaming agent and coupling agent are added dropwise, continue stirring at a speed of 300 rpm for 15 minutes. After the resins are mixed evenly, stop stirring, vacuumize and degas for standby use.
[0029] (2) Accurately weigh methyltetrahydrophthalic anhydride, pour it into the reaction kettle, add flake phthalic anhydride, turn on the stirrer, set the speed to 300 rpm, raise the temperature to 120°C while stirring, wait until the flake phthalic anhydride is completely dissolved, cool to 60°C, add 2,4,6-tris(dimethylaminomethyl)phenol dropwise while stirring, after the addition is complete, set the stirrer speed to 400 rpm, continue stirring for 15 minutes, cool to room temperature, evacuate and degas for later use.
[0030] (3) The resin mixture of step (1) and the curing agent mixture of step (2) are uniformly mixed in a ratio of 100:90, and a high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition is obtained after degassing.
[0031] Comparative Example 1 A hydrogen fuel cell graphite bipolar plate sealing resin composition comprises a resin mixture and a curing agent mixture, wherein the resin mixture comprises 10 parts of bisphenol A epoxy resin, 61.9 parts of bisphenol F epoxy resin, 13 parts of 1,4-butanediol diglycidyl ether, 15 parts of polypropylene glycol diglycidyl ether, and 0.1 part of a defoamer; and the curing agent mixture comprises 99 parts of methyltetrahydrophthalic anhydride and 1 part of 1,8-diaza-bicyclo (5,4,0)-7-undecene lactate.
[0032] The preparation method of the above resin composition is: (1) After accurately weighing bisphenol A epoxy resin, bisphenol F epoxy resin, 1,4-butanediol diglycidyl ether, and polypropylene glycol diglycidyl ether according to the proportion, add them into a container, turn on the stirrer, and stir at a speed of 300 rpm for 15 minutes. After stirring, reduce the stirrer speed to 100 rpm, and then add the defoaming agent dropwise while stirring. After the defoaming agent is added, continue stirring at a speed of 300 rpm for 15 minutes. After the resins are mixed evenly, stop stirring, and vacuum degas for standby use.
[0033] (2) Accurately weigh methyltetrahydrophthalic anhydride, pour it into a container, turn on the stirrer, set the speed to 200 rpm, and add 1,8-diaza-bicyclo (5,4,0)-7-undecene lactate dropwise while stirring. After the addition is completed, set the stirrer speed to 300 rpm and continue stirring for 15 minutes. Stop stirring after the curing agent is evenly mixed, and evacuate the mixture to remove bubbles for later use.
[0034] (3) The resin mixture of step (1) and the curing agent mixture of step (2) are uniformly mixed in a ratio of 100:90, and after degassing, a hydrogen fuel cell graphite bipolar plate sealing resin composition is obtained.
[0035] Comparative Example 2 A hydrogen fuel cell graphite bipolar plate sealing resin composition comprises a resin mixture and a curing agent mixture, wherein the resin mixture comprises 78.5 parts of phenolic epoxy resin, 9 parts of 1,6-hexanediol diglycidyl ether, 11.9 parts of polypropylene glycol diglycidyl ether, 0.1 part of a defoamer, and 0.5 part of a coupling agent; the curing agent mixture comprises 94.2 parts of methyltetrahydrophthalic anhydride, 3.2 parts of carboxyl-terminated polybutadiene, 2.5 parts of 2,4-dimethylimidazole, and 0.1 part of 2,6-di-tert-butyl-p-cresol.
[0036] The preparation method of the above resin composition is: (1) After accurately weighing the phenolic epoxy resin, 1,6-hexanediol diglycidyl ether, and polypropylene glycol diglycidyl ether according to the proportion, add them into a container, turn on the stirrer, and stir at a speed of 300 rpm for 15 minutes. After stirring, reduce the stirrer speed to 100 rpm, and then add the defoamer and coupling agent dropwise while stirring. After the defoamer and coupling agent are added dropwise, continue stirring at a speed of 300 rpm for 15 minutes. Stop stirring after the resin is evenly mixed, and vacuum degas for standby use.
[0037] (2) Accurately weigh methyltetrahydrophthalic anhydride and carboxyl-terminated polybutadiene, pour them into a glass reactor, add 2,4-dimethylimidazole, heat the reactor to 95-100°C, stir while heating, set the speed to 200 rpm, wait until 2,4-dimethylimidazole is completely dissolved, then add 2,6-di-tert-butyl-p-cresol, continue heating and stirring, wait until 2,6-di-tert-butyl-p-cresol is completely dissolved, cool to 25-35°C, add coupling agent dropwise while stirring, after the addition is completed, set the stirrer speed to 300 rpm, continue stirring for 15 minutes, stop stirring after the curing agent is evenly mixed, and evacuate to remove bubbles for later use.
[0038] (3) The resin mixture of step (1) and the curing agent mixture of step (2) are uniformly mixed in a ratio of 100:90, and after degassing, a hydrogen fuel cell graphite bipolar plate sealing resin composition is obtained.
[0039] Performance Testing: The viscosity and heat resistance of the resin compositions in the above embodiments and comparative examples were tested, respectively, and the results are shown in Table 1. It can be seen from Table 1 that the resin composition provided by the embodiment of the present invention has high glass transition temperature and heat deformation temperature and good heat resistance. After the resin compositions in the above embodiments and comparative examples were made into resin samples, the resin samples were boiled in different media at 96°C for 1000 hours to detect the mass change (mass increase rate), and the results are shown in Table 2. The density change of the resin samples was boiled in different media at 96°C for 1000 hours, and the results are shown in Table 3. The hardness change of the resin samples was boiled in different media at 96°C for 1000 hours, and the results are shown in Table 4. The conductivity increase and ion precipitation of the resin samples were boiled in deionized water at 96°C for 1000 hours, and the results are shown in Table 5. It can be seen from Tables 2 to 5 that the resin composition provided by the embodiment of the present invention has good chemical corrosion resistance and acid resistance. In the measured medium, the mass increase rate of the resin composition provided by the embodiment is lower than that of the comparative example, and its conductivity increase and Cl - The precipitation amount is lower than that of the comparative example, and the overall performance is better than that of the comparative example. The acid combination solution in Tables 2 to 4 refers to a combination of dilute sulfuric acid and hydrofluoric acid (hydrofluoric acid concentration 0.1 mmol / L).
[0040] Table 1 Resin viscosity and heat resistance
[0041] In Table 1, X represents poor sealing effect, and O represents good sealing effect; the sealing effect is tested by PT penetration test method, which is a non-destructive testing technology based on the principle of liquid capillary action. This method applies a penetrant containing a dye (in this test, the sealing resin composition is used as a penetrant) to penetrate into the micropores of the graphite bipolar plate, and then uses a developer to adsorb the penetrant in the micropores to the surface of the bipolar plate, and observes the imaging results under a certain light source (such as black light or white light) to evaluate the sealing effect. If there are obvious traces of penetrant on the surface of the bipolar plate, it means that the sealing effect of the resin composition is not good; otherwise, it means that the sealing effect is good.
[0042] Table 2 Mass increase of resin samples boiled in different media at 96℃ for 1000h
[0043] Table 3 Density changes of resin samples in different media at 96℃ for 1000h
[0044] Table 4 Hardness changes of resin samples in different media at 96℃ for 1000h
[0045] Table 5 Ion precipitation of resin samples boiled in deionized water at 96℃ for 1000h
[0046] In Example 1 of the present invention, a low-viscosity alicyclic epoxy resin is selected to be compounded with a bisphenol A epoxy resin to reduce the amount of diluent used, and is matched with an imidazole accelerator with good heat resistance. While retaining the system's low initial viscosity, the resin curing crosslinking density is increased, thereby increasing its glass transition temperature. When the glass transition temperature of the resin is higher, the material not only exhibits better heat resistance, but also the resin cured product has better chemical resistance in different media. The main reason is that the higher the three-dimensional network crosslinking density of the resin, the small molecule chemical medium is not easy to penetrate into the interior of the resin cured product, thereby reducing the impact on the resin cured product; another reason is that when the resin glass transition temperature is higher than the medium temperature, the resin cured product has not yet changed from a glassy state to a high elastic state, and the molecular chain segment activity inside the resin cured product is relatively small, which is easier to resist the influence of the medium on it. Example 2 is to reduce the system viscosity by compounding bisphenol F epoxy resin with bisphenol A epoxy resin, reduce the amount of diluent used, and select tetrahydrophthalic anhydride and methyltetrahydrophthalic anhydride as the curing agent to increase the glass transition temperature.
[0047] Comparing Comparative Example 1 with Comparative Example 2, although the initial mixed viscosity of the two is not much different, the sealing effect of Comparative Example 2 is better than that of Comparative Example 1. The main reason is that the viscosity increase rate of the resin in Comparative Example 1 is too slow at room temperature (e.g. Figure 1 As shown in the figure, the viscosity of the resin on the surface of the graphite plate and in the pores inside the graphite plate is too low when the impregnation is completed. The curing of the resin gel requires a certain temperature condition. During the curing temperature rise stage, the low-viscosity resin is easy to drip from the surface of the graphite plate, resulting in poor sealing effect.
[0048] The above description is only a preferred embodiment of the present invention and is not any formal or substantial limitation of the present invention. It should be pointed out that a person skilled in the art can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention.
Claims
1. A high heat-resistant hydrogen fuel cell graphite bipolar plate sealing resin composition, characterized in that: The resin composition comprises a resin mixture and a curing agent mixture, wherein the weight ratio of the resin mixture to the curing agent mixture is 100:(80-100); wherein the resin mixture comprises 70-90wt% of epoxy resin, 5-30wt% of diluent and 0-2wt% of auxiliary agent; the curing agent mixture comprises 90-99.5wt% of anhydride curing agent, 0.1-5wt% of accelerator and 0-5wt% of auxiliary agent; the diluent is a combination of a glycerol ether diluent and an alcohol diluent; The resin composition needs to meet the following properties: 1) Initial mixed viscosity ≤300mpa.s at 25℃; 2) The gel time of the resin composition at 160°C is ≤5min; 3) After the resin composition is cured at 140-160°C for 1-3 hours, the glass transition temperature is greater than 95°C; and 4) The surface tension of the resin composition is less than 30 mN / m.
2. The resin composition according to claim 1, characterized in that The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, alicyclic epoxy resin, multifunctional epoxy resin, brominated epoxy resin and flexible long-chain toughened epoxy resin, and the epoxy equivalent of the epoxy resin is 100-400 g / equivalent; And / or, the auxiliary agent includes at least one of a coupling agent, a defoaming agent, a toughening agent, a thixotropic agent, a wetting agent, an antioxidant and a leveling agent.
3. The resin composition according to claim 1, characterized in that The glyceryl ether diluent is selected from at least one of benzyl glycidyl ether, butyl glycidyl ether, octyl glycidyl ether, C12-C14 alkyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, dipropylene glycol diglycidyl ether, 1,2-cyclohexanediol diglycidyl ether, 1,4-cyclohexanediol diglycidyl ether, and pentaerythritol tetraglycidyl ether; The alcohol diluent is selected from at least one of benzyl alcohol, low molecular weight polypropylene glycol with a molecular weight of ≤2000 and low molecular weight polyethylene glycol with a molecular weight of ≤500.
4. The resin composition according to claim 1, characterized in that The anhydride curing agent is selected from at least one of phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, C8~C9 olefin succinic anhydride, dodecenyl succinic anhydride, methyl nadecanide, hydrogenated methyl nadecanide, tung oil anhydride, maleic anhydride, glutaric anhydride and cross-methylene tetrahydrophthalic anhydride.
5. The resin composition according to claim 1, characterized in that The accelerator is selected from o-hydroxybenzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, trioleate of 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 1,8-diaza-bicyclo(5,4,0)-7-undecene, 1,8-diaza-bicyclo(5,4,0)-7-undecene octanoate, 1,8-diaza-bicyclo(5,4,0)-7-undecene lactate, 1,8-diaza-bicyclo(5,4,0)-7-undecene phenolate, 1,8-diaza-bicyclo(5,4,0)-7-undecene phenolate. -7-undecene toluenesulfonate, 1,8-diaza-bicyclo (5,4,0)-7-undecenephthalate, 1,5-diazabicyclo [4.3.0] -5-nonene, benzyltriethylammonium chloride, tetraethylammonium bromide, tetrabutylammonium bromide, tetraphenylphosphonium bromide, tetrabutylphosphonium acetate, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-phenyl-2-methylimidazole, 1-methylimidazole, 2-methylimidazole, 2,4-dimethylimidazole and 2,6-di-tert-butyl-p-cresol.
6. The resin composition according to claim 1, characterized in that The resin mixture comprises 70-80 parts of bisphenol A epoxy resin, 10-20 parts of alicyclic epoxy resin, 3-5 parts of 1,4-butanediol diglycidyl ether, 3-10 parts of polypropylene glycol, 0.1-0.3 parts of defoaming agent, and 0.05-0.2 parts of coupling agent; the curing agent mixture comprises 90-99 parts of methyltetrahydrophthalic anhydride and 1-10 parts of 1-cyanoethyl-2-ethyl-4-methylimidazole.
7. The resin composition according to claim 1, characterized in that The resin mixture comprises 40-60 parts of bisphenol A epoxy resin, 30-40 parts of bisphenol F epoxy resin, 9-11 parts of C12-C14 alkyl glycidyl ether, 4-6 parts of polyethylene glycol, 0.05-0.2 parts of defoaming agent, and 0.1-0.3 parts of coupling agent; the curing agent mixture comprises 85-95 parts of methyltetrahydrophthalic anhydride, 5-15 parts of phthalic anhydride, and 0.5-2 parts of 2,4,6-tris(dimethylaminomethyl)phenol.
8. Use of the resin composition according to any one of claims 1 to 7 in sealing graphite bipolar plates.
Citation Information
Patent Citations
Fuel cell pore sealing method
CN106450375A
Extrusion of graphite bodies
CN1524066A
Method for producing bipolar plate for fuel cell
KR1020050118047A
Carbon-filled polymer composite bipolar plates for proton exchange membrane fuel cells
US20100216037A1
Cited By
High-heat-resistance fuel cell flexible graphite bipolar plate micropore plugging agent
CN119842005A
High-heat-resistant fuel cell flexible graphite bipolar plate pore sealing agent
CN119842005B
